Dampak Nilai Fundamental Terhadap Harga Saham Pada Sektor Perbankan Tahun 2020 - 2022 - Muchlis, Muchlis; Tampati, Tigran Aslam (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2024)
This research examines the impact of fundamental values on share prices in Indonesian banking companies from 2020 to 2022. It investigates the influence of earnings per share, book value per share, and the composite stock price index on share prices, with the debt-to-equity ratio as a control variable. Using purpose sampling, 43 companies were observed. The findings suggest that earnings per share, book value per share, and the composite stock price index influence share prices, while the debt-to-equity ratio does not. It advises banks to focus on increasing net profits by optimizing products and services and managing expenses and non-performing loans. Additionally, banks should monitor asset growth, which positively correlates with share price increases.